The Role of Content Marketing and Live Streaming in Improving Decisions to Purchase Skincare Products on the Shopee Application - Silvia Septiani; Gahefira Nur Fatimah (Journal of Managiere and Business, 2024)
The rapid development of technology, indisputably advancing, has led toimprovements across various industries. This progress has also had an impact onadvancements within the industrial sector. According to the current phenomenon,many marketers still lack understanding of the opportunities available, particularlyregarding the Live Streaming feature for the products they market. The objective of this research is to understand the impact of live streaming and content marketing on the purchasing decisions of Shopee users. One hundred respondents were involved in this study. Respondents were selected through purposive sampling. The data were analyzed using the SPSS version 25 method. The results of this study indicate that content marketing and live streaming have a positive and significant impact on purchasing decisions on the Shopee application. Furthermore, based on the determination test results (R2) of 0.732, equivalent to 73.2%, while the other variables not included in this study influence the remaining 26.8%.